Method for directional construction of non-noble metal catalysts with high ratio of alloyed diatomic pairs

By oriented construction of a non-precious metal catalyst with high proportion alloyed diatom pairs, the problem of low diatom ratio in diatom catalysts in the prior art is solved, the catalytic activity and stability are improved, and the performance of the hydroxide proton exchange membrane fuel cell is significantly improved.

CN119170813BActive Publication Date: 2025-04-18SHENZHEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411498707.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-18
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing diatomic catalyst (DACs) synthesis method is difficult to ensure that the proportion of diatom pairs in the catalyst is high, resulting in insufficient catalytic activity and stability, which limits its application in hydrogen proton exchange membrane fuel cells (PEMFCs).

Method used

By using a method of directed construction of a high proportion of alloyed diatom pairs, an alloyed diatom catalyst with high density and orderly distribution is formed by preparing the precursor ZIF-8, preparing a metal salt solution, adsorption and pyrolysis treatment.

Benefits of technology

The intrinsic catalytic activity and stability of the catalyst are improved, efficient oxygen reduction catalysis is achieved, and the maximum power density of the hydroxide proton exchange membrane fuel cell is improved, exceeding the performance of most non-precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170813B_ABST
    Figure CN119170813B_ABST
Patent Text Reader

Abstract

A method for directionally constructing a non-precious metal catalyst with a high proportion of alloyed diatomic pairs, which relates to a method for preparing a non-precious metal catalyst, is intended to solve the technical problems of low proportion of diatomic pairs and poor catalytic effect in existing diatomic catalysts. This method uses small cyanamide molecules and two transition metal ions to prepare a salt solution pre-anchored with dimetallic ions, then adsorbs the ZIF‑8 powder onto the salt solution, anneals it at high temperature under a protective atmosphere after drying, and obtains a non-precious metal catalyst loaded with a high proportion of alloyed diatomic pairs. The maximum power density of the hydrogen-oxygen proton exchange membrane fuel cell prepared using the catalyst is 1070mW cm in a H2 / O2 environment. ‑2 , the maximum power density in Air / H2 environment reaches 624mW cm ‑2 , which can be used in the field of hydrogen proton exchange membrane fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a non-noble metal catalyst, and belongs to the field of heterogeneous catalysis. Background Art

[0002] With the diversified development of energy architecture, the development of hydrogen proton exchange membrane fuel cells (PEMFCs) with hydrogen energy as an important application terminal can not only accelerate the optimization of the energy system, but also take into account the development of the ecological environment with the advantages of complete cleanliness and zero pollution. However, in commercial PEMFCs, although precious metal Pt-based catalysts can be used to reduce the high overpotential of the cathode oxygen reduction reaction (ORR), the high cost of Pt-based catalysts and their susceptibility to CO poisoning have greatly limited the further commercial development and application of PEMFCs. At present, single-atom catalysts (SACs) prepared based on transition metals (Fe, Co, Mn, Ni, Cu, etc.) and N-co-doped carbon-based materials (MNCs) have shown great heterogeneous catalytic potential, especially in the ORR process in PEMFCs. Considering that molecules always exist in the form of multiple atoms in the heterogeneous catalytic process, such as oxygen (OO) in the ORR process and carbon dioxide participating in the carbon dioxide reduction (CO2RR) reaction, diatomic catalysts (DACs) evolved based on SACs have a structural model that is kinetically and thermodynamically easier to complete catalysis efficiently. In addition, a large number of research works have demonstrated the high catalytic activity and high stability of DACs, and they have great potential to replace Pt-based catalysts in PEMFCs.

[0003] The existing preparation methods of DACs make it difficult to ensure that the diatomic pairs in the catalyst prepared after the precursor pyrolysis exist in a high proportion, mainly in the form of SACs and DACs coexisting. Therefore, there is an urgent need for a synthesis method of effectively synthesizing a high proportion of DACs catalysts, which can not only improve the intrinsic catalytic activity and stability of the catalyst, but also accelerate the development of more competitive catalysts. Summary of the invention

[0004] The present invention aims to solve the technical problem of low ratio of diatomic pairs in the catalysts obtained by the existing synthesis methods of diatomic catalysts (DACs), and provide a method for directionally constructing non-precious metal catalysts with high ratio of alloyed diatomic pairs.

[0005] The method of the present invention for directional construction of a non-noble metal catalyst with high proportion of alloyed diatomic pairs comprises the following steps:

[0006] 1. Preparation of precursor ZIF-8;

[0007] 2. Prepare a metal salt solution: add two soluble salts of transition metals M1 and M2 to a mixed solution of deionized water and anhydrous ethanol at a molar ratio of 1:(0.9-1.1) between the two metal ions, then add cyanamide (CH2N2) to the mixed solution, wherein the total mass ratio of the two soluble salts of transition metals M1 and M2 to the mass ratio of cyanamide is 1:(1.8-2.5), and ultrasonicate the mixed solution at a temperature of 30-40°C for 30-40 minutes to obtain a salt solution pre-anchored with M1 and M2; wherein the soluble salts of transition metals M1 and M2 are nitrates or chlorides of Fe, Co, Ni, Zn, Cu, Mn or Cr; and the transition metals Fe, Co, Ni, Zn, Cu, Mn or Cr have coordination ability;

[0008] 3. Immerse the ZIF-8 powder in the salt solution pre-anchored with M1 and M2 for adsorption; or drip the salt solution pre-anchored with M1 and M2 into the ZIF-8 powder for grinding and adsorption, so that the salt solution pre-anchored with M1 and M2 ions is dispersed on the ZIF-8 powder, and then vacuum dried to obtain the M1-M2@ZIF-8 precursor;

[0009] Fourth, the M1-M2@ZIF-8 precursor is placed in a tube furnace, heated to 1000-1100°C under a protective atmosphere and maintained for 1-3 hours for high temperature annealing, and then cooled to room temperature to obtain a non-precious metal catalyst with ordered alloyed diatomic pairs. The alloyed diatomic pairs in the catalyst are distributed on the substrate in a monodisperse form.

[0010] Furthermore, the precursor ZIF-8 described in step 1 is prepared by a room temperature stirring static method, and the specific steps are as follows:

[0011] (1) First, zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole were weighed in a molar ratio of 1:(4-8); 2-methylimidazole was dissolved in anhydrous methanol and completely dissolved with ultrasound assistance until clear, which was recorded as solution A; zinc nitrate hexahydrate was then dissolved in anhydrous methanol and completely dissolved with ultrasound assistance, which was recorded as solution B;

[0012] (2) Pour solution B into solution A to obtain a precursor solution; and heat the precursor solution at room temperature at 900 to 1000 r min -1 Stirring at a high speed for 1 to 2 hours to form enough ZIF-8 crystal nuclei, and then letting it stand for 12 to 22.5 hours to allow the ZIF-8 grains to grow uniformly to obtain a product mixed solution;

[0013] (3) The product mixture was washed with anhydrous methanol and then centrifuged at a speed of 6000-6500 rmin. -1Stir for 5 to 8 minutes, then stir at a speed of 9000 to 10000 r min -1 Stir for 10 to 15 minutes under the conditions of 9000 to 10000 r min -1 The mixture is stirred for 15 to 20 minutes to fully remove the unreacted metal salt and leave more micropores and mesopores for the subsequent adsorption of trace metal salt solvents; after washing, the product is dried at 70 to 80°C for 5 to 6 hours, and after drying and cooling, it is taken out and ground to obtain ZIF-8 powder; the powder is bottled and placed in a vacuum drying oven for use; the ZIF-8 powder prepared by the room temperature stirring static method is kept in a vacuum drying oven to ensure that there are enough active sites attached to the dispersed metal salt solution to ensure the synthesis of the alloyed diatomic pair catalyst.

[0014] Furthermore, in step (1), the concentration of 2-methylimidazole is 0.03 to 0.045 g / mL; the concentration of zinc nitrate hexahydrate is 0.03 to 0.045 g / mL;

[0015] Furthermore, in step (2), the Zn 2+ The concentration is 0.4~0.8mol / L.

[0016] Furthermore, in step 3, every 100 mg of ZIF-8 powder was adsorbed with 100 μL of the salt solution pre-anchored with M1 and M2;

[0017] Furthermore, the vacuum drying in step 3 is performed at a temperature of 30 to 35° C. for 0.5 to 1 h;

[0018] Furthermore, the protective atmosphere in step 4 is nitrogen, argon, or a hydrogen-argon mixed gas with a hydrogen volume content of 5% to 10%.

[0019] Furthermore, the amount of the protective gas introduced in step 4 is 20-30 ml / min;

[0020] Furthermore, the temperature increase in step 4 is 10-30°C min -1 Too low or too high a heating rate can easily cause the loss of carbon and nitrogen.

[0021] The method of the non-precious metal catalyst for the directional construction of high-proportion alloyed diatomic pairs of the present invention is based on the process of preparing single-atom catalysts by atomic-level chelation of small molecules of cyanamide and microphase solid-liquid impregnation etching. The introduction of cyanamide can first provide more nitrogen sources, prompting the ZIF-8 pyrolysis process to anchor more transition metal sources, and improve the density of catalytic active sites while improving the dispersion of transition metal atoms. At the same time, by virtue of the electronic properties of transition metals Fe, Co, Ni, Zn, Cu, Mn or Cr themselves, they can form Prussian blue analogs, fully chelate with cyanamide in a mixed solvent of ethanol and water, and complete the pre-coupling of metal salt atomic pairs based on the ion coupling effect, and then complete the preparation of highly dispersed high-density alloyed diatomic pairs of electrocatalysts by adsorption pyrolysis; wherein, the pre-vacuum treatment of the precursor, the chelation dispersion of the metal salt and the subsequent pyrolysis temperature of the metal salt ZIF-8 precursor are all necessary conditions to ensure the preparation of the catalyst of the present invention. This diatomic active site can exhibit excellent phase transport ability while taking into account high charge transfer ability, thereby increasing the active site density of the catalyst and providing a basis for achieving high performance of diatomic catalysts as a whole.

[0022] The hydrogen-oxygen proton exchange membrane fuel cell prepared by the non-precious metal catalyst of the present invention exhibits a high performance of up to 1070 mW cm in a H2 / O2 environment. -2 The maximum power density (P max ), in Air / H2 environment, the maximum power density reaches 624mWcm -2 , the maximum power density exceeds that of most reported non-precious metal catalysts. The catalyst of the present invention can be used in the field of hydrogen-oxygen proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of the ZIF-8 precursor prepared in step 1 of Example 1 and Comparative Example 1.

[0024] Figure 2 The Fe and Co pre-anchored salt solution [Fe 3+ Co 2+ (CN)6], the Fe pre-anchored salt solution prepared in step 2 of comparative example 1 [Fe(CN)6 3+ ], Co pre-anchored salt solution [Co(CN)6 2+ ] and optical images of a mixed solution of iron nitrate and cobalt nitrate (FeCo).

[0025] Figure 3 The Fe and Co pre-anchored salt solution [Fe 3+ Co 2+(CN)6], the Fe pre-anchored salt solution prepared in step 2 of comparative example 1 [Fe(CN)6 3+ ], Co pre-anchored salt solution [Co(CN)6 2+ ] and UV-visible absorption spectra of iron nitrate and cobalt nitrate mixed solution (FeCo).

[0026] Figure 4 X-ray diffraction spectra of T-FeCo-NC prepared in Example 1, R-FeCo-NC prepared in Comparative Example 1, and original ZIF-8.

[0027] Figure 5 X-ray diffraction spectra of T-FeCo-NC prepared in Example 1, R-FeCo-NC prepared in Comparative Example 1, S-Fe-NC prepared in Comparative Example 2, and T-FeCo-NC (without NC) prepared in Comparative Example 3;

[0028] Figure 6 TEM images of T-FeCo-NC prepared in Example 1 at different resolutions and element distribution maps of HR-TEM.

[0029] Figure 7 AC-HAADF-STEM image, energy loss spectrum EELS and element distribution map of T-FeCo-NC prepared in Example 1.

[0030] Figure 8 It is a comparison chart of Fourier X-ray extended edge absorption spectra FT-EXAFS of Example T-FeCo-NC and R-FeCo-NC prepared in Comparative Example 1.

[0031] Fig. 9 The k-space fitting diagram of the X-ray absorption spectra of Example T-FeCo-NC and Comparative Example R-FeCo-NC.

[0032] Fig.10 The examples T-FeCo-NC (a) and R-FeCo-NC (b) are 57 Fe Mössbauer spectrum.

[0033] Fig.11 Polarization-power density curves of Example T-FeCo-NC and Comparative Example R-FeCo-NC under 2.0 bar, H2-O2 and H2-Air conditions. DETAILED DESCRIPTION

[0034] The beneficial effects of the present invention are verified by the following examples.

[0035] Example 1: The method for directional construction of a non-noble metal catalyst with a high proportion of alloyed diatomic pairs in this example is carried out according to the following steps:

[0036] 1. The precursor ZIF-8 was prepared by room temperature stirring static method. The specific steps are as follows:

[0037] (1) First, 4.928 g of 2-methylimidazole was dissolved in 120 mL of anhydrous methanol solution and completely dissolved with the aid of ultrasound until it was clear, which was recorded as solution A; then 4.464 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was dissolved in 120 mL of anhydrous methanol solution and completely dissolved with the aid of ultrasound, which was recorded as solution B;

[0038] (2) Pour solution B into solution A and heat at 900 r min at room temperature. -1 The mixture was stirred at a speed of 90 min to form enough ZIF-8 nuclei, and then allowed to stand for 22.5 h to allow the ZIF-8 grains to grow uniformly, thereby obtaining a product mixture. In this step, the initial stirring of 900 for 90 minutes allowed the ZIF-8 seeds to be produced quickly, and then the mixture was allowed to stand for 22.5 hours to allow the ZIF-8 grains to gradually increase in size and reach a suitable size.

[0039] (3) The product mixture was washed three times with anhydrous methanol and then centrifuged at a speed of 6000 r min. -1 Stir for 5 min at a speed of 10000 r min -1 Stir for 10 min at a speed of 10000 rmin. -1 Stir for 15 minutes under the conditions of 100 ° C. to fully remove the unreacted metal salt and leave more micropores and mesopores for subsequent adsorption of trace metal salt solvents; after washing, dry the product at a temperature of 80 ° C. for 6 hours, and after drying and cooling, take it out and grind it to obtain ZIF-8 powder; bottle the ZIF-8 powder and put it into a vacuum drying oven for standby; keep the prepared ZIF-8 powder in a vacuum drying oven to ensure that there are enough active sites attached to the dispersed metal salt solution to ensure the synthesis of the alloyed diatomic pair catalyst;

[0040] 2. Prepare the metal salt solution: first weigh 30 mg Fe(NO3)3·9H2O, 20 mg cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 100 mg CH2N2 and dissolve them in a mixed solution of 400 μL deionized water and 400 μL anhydrous ethanol, and treat the mixed solution by ultrasonic treatment at 35°C for 30 min to obtain a salt solution pre-anchored with Fe and Co;

[0041] 3. The ZIF-8 powder was placed in a vacuum drying oven at a temperature of 35°C and vacuum dried for 4 hours. Then, 300 μL of the pre-anchored salt solution of Fe and Co was dripped into 300 mg of ZIF-8 powder in an agate mortar in 6 times of 50 μL each time. Each time the Fe and Co pre-anchored salt solution was dripped into ZIF-8, it was stirred, dispersed and ground evenly in the mortar to make the pre-anchored Fe and Co ion salt solution dispersed and adsorbed on the ZIF-8 powder. Then, it was placed in a vacuum drying oven at a temperature of 30°C and vacuum dried for 4 hours to obtain the Fe-Co@ZIF-8 precursor.

[0042] Fourth, the Fe-Co@ZIF-8 precursor was placed in a tube furnace, argon gas was introduced into the tube furnace at a flow rate of 25 ml / min for protection, and the tube furnace was set at 20 °C min -1 The temperature was raised to 1050 °C and maintained for 1 h for high temperature annealing treatment, and then cooled to room temperature to obtain a non-precious metal catalyst with ordered alloyed diatomic pairs, which was recorded as T-FeCo-NC.

[0043] Comparative Example 1: In this comparative example 1, metal ions are anchored separately during the preparation process. The preparation method of the catalyst in this comparative example is as follows:

[0044] 1. Precursor ZIF-8 was prepared by room temperature stirring static method, and the specific steps were the same as step 1 of Example 1;

[0045] 2. Preparation of metal salt solution:

[0046] 30 mg Fe(NO3)3·9H2O and 60 mg CH2N2 were weighed and dissolved in 400 μL deionized water and 400 μL anhydrous ethanol, and ultrasonicated at 35 °C for 30 min to obtain a Fe pre-anchored salt solution, which was recorded as A1;

[0047] Weigh 20 mg Co(NO3)2·6H2O and 40 mg CH2N2 and dissolve them in 400 μL deionized water and 400 μL anhydrous ethanol, and ultrasonicate at 35 °C for 30 min to obtain a Co pre-anchored salt solution, which is recorded as B1;

[0048] 3. Place the ZIF-8 powder in a vacuum drying oven at a temperature of 35°C for 4 hours, weigh 300 mg of the vacuum-dried ZIF-8 powder, first drop 50 μL of A1 into the ZIF-8 powder for grinding and adsorption, and then drop 50 μL of B1 into the ZIF-8 powder for grinding and adsorption; repeat the operation of dropping A1 and dropping B1 twice, and complete the operation of dropping a total of 300 μL of metal salt solution into 300 mg of ZIF-8 powder in the order of A1-B1-A1-B1-A1-B1, and then place it in a vacuum drying oven at a temperature of 30°C for vacuum drying for 4 hours to obtain a precursor;

[0049] 4. Place the precursor in a tube furnace, introduce argon gas at a flow rate of 25 ml / min into the tube furnace for protection, and set the tube furnace at 20 °C min -1 The temperature was raised to 1050°C and maintained for 1 h for high temperature annealing treatment, then cooled to room temperature to obtain a catalyst, which was recorded as R-FeCo-NC.

[0050] Comparative Example 2: In this comparative example, only iron ions are anchored during the preparation process. The preparation method of the catalyst in this comparative example is as follows:

[0051] 1. Precursor ZIF-8 was prepared by room temperature stirring static method, and the specific steps were the same as step 1 of Example 1;

[0052] 2. Preparation of metal salt solution:

[0053] First, 30 mg Fe(NO3)3·9H2O and 100 mg CH2N2 were weighed and dissolved in a mixed solution of 400 μL deionized water and 400 μL anhydrous ethanol. The mixed solution was ultrasonically treated at 35°C for 30 min to obtain a Fe pre-anchored salt solution.

[0054] 3. The ZIF-8 powder was placed in a vacuum drying oven at 35°C for 4 hours, and then 300 μL of the Fe pre-anchored salt solution was dripped into 300 mg of ZIF-8 powder in an agate mortar in 6 times of 50 μL each time. Each time the Fe pre-anchored salt solution was dripped into ZIF-8, it was stirred, dispersed and ground evenly in the mortar to make the pre-anchored Fe ion salt solution dispersed and adsorbed on the ZIF-8 powder, and then placed in a vacuum drying oven at 30°C for 4 hours to obtain the Fe@ZIF-8 precursor.

[0055] Fourth, the Fe@ZIF-8 precursor was placed in a tube furnace, argon gas was introduced into the tube furnace at a flow rate of 25 ml / min for protection, and the tube furnace was set at 20 °C min -1 The temperature was raised to 1050°C and maintained for 1 h for high temperature annealing treatment, then cooled to room temperature to obtain a catalyst, which was recorded as S-Fe-NC.

[0056] Comparative Example 3: In this comparative example, cyanamide was not used to anchor metal ions during the preparation process. The preparation method of the catalyst in this comparative example is as follows:

[0057] 1. Precursor ZIF-8 was prepared by room temperature stirring static method, and the specific steps were the same as step 1 of Example 1;

[0058] 2. Prepare the metal salt solution: first weigh 30 mg Fe(NO3)3·9H2O and 20 mg cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and dissolve them in a mixed solution of 400 μL deionized water and 400 μL anhydrous ethanol, and treat the mixed solution by ultrasonic treatment at 35°C for 30 min to obtain a Fe, Co mixed salt solution;

[0059] 3. Place the ZIF-8 powder in a vacuum drying oven at 35°C and vacuum dry for 4 hours, then drip 300 μL of the Fe, Co mixed salt solution into 300 mg of ZIF-8 powder in an agate mortar 6 times, 50 μL each time. After each drop of the salt solution into the ZIF-8, stir and disperse it in the mortar and grind it evenly, so that the salt solution is dispersed and adsorbed on the ZIF-8 powder, and then place it in a vacuum drying oven at 30°C and vacuum dry it for 4 hours to obtain a precursor;

[0060] 4. Place the precursor in a tube furnace, introduce argon gas at a flow rate of 25 ml / min into the tube furnace for protection, and set the tube furnace at 20 °C min -1 The temperature was raised to 1050°C and maintained for 1 h for high temperature annealing treatment, and then cooled to room temperature to obtain a catalyst, which was recorded as T-FeCo-NC (without NC).

[0061] The SEM images of the ZIF-8 precursor prepared in step 1 of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, from Figure 1 It can be seen that the size of the ZIF-8 grains is about 250nm to 350nm. A too small ZIF-8 precursor is not conducive to the stability of the morphology after cyanamide etching growth during the pyrolysis process. An overly large ZIF-8 makes the specific surface area per unit volume too small and cannot achieve the ideal active site attachment area. The ZIF-8 grain size prepared in Example 1 is suitable.

[0062] The Fe and Co pre-anchored salt solution prepared in step 2 of Example 1 [Fe 3+ Co 2+ (CN)6], the Fe pre-anchored salt solution prepared in step 2 of comparative example 1 [Fe(CN)6 3+ ], Co pre-anchored salt solution [Co(CN)6 2+ ] and the optical images of the mixed solution of iron nitrate and cobalt nitrate (FeCo) Figure 2 The UV-visible absorption spectrum is shown in Figure 3 As shown, the mixed solution of iron nitrate and cobalt nitrate (FeCo) is prepared by dissolving 30 mg Fe(NO3)3·9H2O and 20 mg Co(NO3)2·6H2O in 400 μL deionized water and 400 μL anhydrous ethanol. Figure 2It can be seen that compared with the FeCo salt solution without the addition of cyanamide, the introduction of small molecules of cyanamide can chelate well with the metal salt solution to complete the pre-dispersion of the precursor. Figure 3 It can be seen that compared with the pure Fe 3+ Co 2+ For solution (absorption peak at 217.44nm),

[0063] [Fe 3+ Co 2+ The absorption peak of the complex [Fe(CN)6] is between 232.26nm and 243.66nm, which is close to and greater than the characteristic values ​​of 236.71nm and 237.96nm. 3+ Co 2+ (CN)6] complex, the electron clouds of Fe-Co overlapped, forming a relatively stable [Fe 3+ Co 2+ (CN)6] complex.

[0064] The X-ray diffraction spectra of T-FeCo-NC prepared in Example 1, R-FeCo-NC prepared in Comparative Example 1 and original ZIF-8 are as follows: Figure 4 As shown. Figure 4 It can be seen that metal precursors can be adsorbed on ZIF-8 without affecting the structure of ZIF-8.

[0065] The X-ray diffraction spectra of T-FeCo-NC prepared in Example 1, R-FeCo-NC prepared in Comparative Example 1, S-Fe-NC prepared in Comparative Example 2, and T-FeCo-NC (without NC) prepared in Comparative Example 3 are as follows: Figure 5 As shown. Figure 5 It can be seen that when there is no effect of cyanamide, there are obvious alloy Co3Fe7 metal particles in the produced catalyst, while there is no metal particle diffraction peak in the catalyst obtained by cyanamide coordination anchoring, which indirectly shows that the metal in the catalyst exists in the form of atomic dispersion, proving the high efficiency of cyanamide coordination anchoring in this method.

[0066] The TEM images of T-FeCo-NC prepared in Example 1 at different resolutions and the element distribution images of HR-TEM are shown in FIG. Figure 6 As shown, ac is the TEM image with different resolutions, and d is the element distribution map of HR-TEM. Figure 6 It can be seen that there are no metal clusters in the catalyst T-FeCo-NC prepared in Example 1.

[0067] The AC-HAADF-STEM image, energy loss spectrum EELS and element distribution map of T-FeCo-NC prepared in Example 1 are as follows: Figure 7 As shown, ac is the AC-HAADF-STEM image, d is the energy loss spectrum EELS corresponding to the blue box a in figure c, and e is the element distribution map of the corresponding area. Figure 7 It can be seen that the T-FeCo-NC catalyst prepared in Example 1 exists in the form of Fe-Co atomic pairs, without metal clusters, and the prepared catalyst does not contain metal nanoparticles. The energy dispersive X-ray spectroscopy (EDS) results show that a large amount of Fe and Co are highly dispersed on the carbon support in the form of atomic pairs, and the N element is evenly distributed in the entire carbon substrate.

[0068] Figure 8 It is a comparison diagram of Fourier X-ray extended edge absorption spectra FT-EXAFS of T-FeCo-NC prepared in Example 1 and R-FeCo-NC prepared in Comparative Example 1. Figure 8 The results show that the T-FeCo-NC of Example 1 has obvious Fe-N / Co-N and Fe-Co peaks, indicating that it is a catalyst of alloyed Fe-Co diatomic atoms, and the ratio of Fe-N / Co-N to Fe-Co peak intensity is 1.22:1, which is significantly lower than that of the R-FeCo-NC catalyst, indicating that the catalyst contains a high proportion of Fe-Co bonds.

[0069] Fig. 9 The k-space fitting diagram of the X-ray absorption spectra of Example T-FeCo-NC and Comparative Example R-FeCo-NC is shown in FIG. Fig. 9 a and c are R-FeCo-NC prepared in Comparative Example 1, b and d are T-FeCo-NC prepared in Example 1, Fig. 9 From the coordination fitting results, it can be seen that almost all Fe and Co in the T-FeCo-NC catalyst form Fe-Co bonds, while the Fe-Co bonds in Comparative Example 1 are relatively low. It can be seen that the pre-coupling of metal salt atom pairs based on the chelation effect of monocyanamide and the ion coupling effect can prepare highly dispersed high-density alloyed diatomic pair electrocatalysts.

[0070] Fig.10 is the T-FeCo-NC of Example 1 and the R-FeCo-NC of Comparative Example 1 57 Fe Mössbauer spectrum, where a is T-FeCo-NC and b is R-FeCo-NC of Comparative Example 1. Fig.10 It can also be seen that compared with the R-FeCo-NC catalyst with only D2 and D3 doublet peaks, the T-FeCo-NC exhibits a Fe-Co six-line peak with an area share of just close to 50%, indicating that a high proportion of alloyed Fe-Co atomic pairs exists in the T-FeCo-NC catalyst.

[0071] In order to test and verify the electrochemical performance of the T-FeCo-NC catalyst of Example 1 and the R-FeCo-NC catalyst of Comparative Example 1, the catalysts T-FeCo-NC and R-FeCo-NC were applied to the cathode catalyst layer of hydrogen proton exchange membrane fuel cells (PEMFCs). The specific method of assembling hydrogen proton exchange membrane fuel cells using T-FeCo-NC and R-FeCo-NC as cathode catalysts is as follows:

[0072] (1) Preparation of cathode catalyst layer: 28 mg of catalyst was weighed and dispersed in a mixed solution containing 30 μl of deionized water, 296 μl of isopropanol, and 425 μl of 5% Nafion resin to form a cathode catalyst slurry; the cathode catalyst slurry was coated on a hydrophobic treated carbon paper by spraying to form a cathode catalyst layer; based on the area of ​​the carbon paper, the catalyst loading in the cathode catalyst layer was 4 mg cm -2 , the content of Nafion resin in the cathode catalyst layer is 41%;

[0073] (2) Preparation of anode catalyst layer: 140 mg of 40% commercial carbon-supported platinum catalyst was weighed and dispersed in a mixed solution of 2.58 ml of water, 2.58 ml of isopropanol, and 2.41 ml of 5% Nafion resin to form an anode catalyst slurry, and the anode catalyst slurry was coated on a hydrophobic treated carbon paper by spraying to form an anode catalyst layer. The loading amount of the commercial carbon-supported platinum catalyst in the anode catalyst layer was 0.1 mg cm based on the area of ​​the carbon paper. -2 , the content of Nafion resin in the anode catalyst layer is 50%;

[0074] (3) Cell assembly: The cathode catalyst layer and the anode catalyst layer are placed on both sides of the proton exchange membrane and hot pressed at a temperature of 120°C, a pressure of 0.8 MPa and a time of 120 seconds to obtain a membrane electrode; the membrane electrode is assembled in a hydrogen proton exchange membrane fuel device to obtain a hydrogen proton exchange membrane fuel cell.

[0075] The assembled hydrogen proton exchange membrane fuel cell was tested under the conditions of temperature of 60°C, back pressure of 2 bar, 100% humidification of gas, hydrogen flow rate of 0.4 slpm, and oxygen flow rate of 1 slpm. The polarization curve of the hydrogen proton exchange membrane fuel cell obtained is shown in Fig.11 As shown. Fig.11 It can be seen that the assembled fuel cell, under the H2 / O2 pressure of 2.0 bar, the T-FeCo-NC prepared in Example 1 and the R-FeCo-NC prepared in Comparative Example 1 showed a high power of 1070 mW cm -2 and 733mWcm -2 The maximum power density (P max), further demonstrating the excellent PEMFCs performance of the Fe-Co all-atom pair. Most importantly, the T-FeCo-NC of Example 1 also exhibited a power of 624 mW cm in the H2 / Air environment. -2 High P max At the same time, the P of R-FeCo-NC prepared in Example 1 max 518 mW cm -2 The maximum power density of T-FeCo-NC prepared in Example 1 exceeds that of most reported non-precious metal catalysts.

[0076] The method for directional construction of high-density ordered alloyed diatoms of the present invention is to construct a pre-anchored dimetallic precursor based on the chelation of monocyanamide and the ion coupling effect, and to obtain an alloyed diatomic catalyst by high-temperature pyrolysis of the zeolite imidazolate framework (ZIFs) pre-adsorbed with the transition metal precursor. The catalyst prepared by the present invention has a very high proportion of M1-M2 (wherein M1 and M2 can be 3d-coordinated transition metals Fe, Co, Mn, Ni, Cu, Zn and other homonuclear or heteronuclear non-precious transition metals with empty electron orbitals) as catalytic active centers on the NC substrate. Based on the stable metal bonds between the transition metals in the alloyed diatoms, the catalyst can exhibit extremely high oxygen reduction catalytic activity under acidic conditions.

Claims

1. A method for directional construction of a non-precious metal catalyst with high proportion of alloyed diatomic pairs, characterized in that The method comprises the following steps:

1. Preparation of precursor ZIF-8; 2. preparing a metal salt solution: adding two soluble salts of transition metals M1 and M2 to a mixed solution of deionized water and anhydrous ethanol at a molar ratio of 1:(0.9-1.1) of the two metal ions, and then adding cyanamide to the mixed solution, wherein the total mass ratio of the soluble salts of the two transition metals M1 and M2 to the mass ratio of cyanamide is 1:(1.8-2.5), and ultrasonicating the mixed solution at a temperature of 30-40°C for 30-40 minutes to obtain a salt solution pre-anchored with M1 and M2; wherein the soluble salts of the transition metals M1 and M2 are nitrates or chlorides of Fe, Co, Ni, Zn, Cu, Mn or Cr; 3. Immerse the ZIF-8 powder in the salt solution pre-anchored with M1 and M2 for adsorption; or drip the salt solution pre-anchored with M1 and M2 into the ZIF-8 powder for grinding and adsorption, so that the salt solution pre-anchored with M1 and M2 ions is dispersed on the ZIF-8 powder, and then vacuum dried to obtain the M1-M2@ZIF-8 precursor; Fourth, the M1-M2@ZIF-8 precursor is placed in a tubular furnace, heated to 1000-1100°C under a protective atmosphere and maintained for 1-3 hours for high temperature annealing treatment, and then cooled to room temperature to obtain a non-precious metal catalyst with ordered alloyed diatomic pairs.

2. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 1, characterized in that: The precursor ZIF-8 described in step 1 is prepared by a room temperature stirring static method, and the specific steps are as follows: (1) First, zinc nitrate hexahydrate and 2-methylimidazole are weighed in a molar ratio of zinc nitrate hexahydrate to 2-methylimidazole of 1:(4-8); 2-methylimidazole is dissolved in anhydrous methanol and completely dissolved with ultrasound assistance until it becomes clear, which is recorded as solution A; zinc nitrate hexahydrate is then dissolved in anhydrous methanol and completely dissolved with ultrasound assistance, which is recorded as solution B; (2) pouring solution B into solution A to obtain a precursor solution; The precursor solution was stirred at room temperature at 900-1000 rmin -1 Stirring at a high speed for 1 to 2 hours to form enough ZIF-8 crystal nuclei, and then letting it stand for 12 to 22.5 hours to allow the ZIF-8 grains to grow uniformly to obtain a product mixed solution; (3) The product mixture was washed with anhydrous methanol and then centrifuged at a speed of 6000-6500 r min. -1 Stir for 5 to 8 minutes, then stir at a speed of 9000 to 10000 r min -1 Stir for 10 to 15 minutes under the conditions of 9000 to 10000 r min -1 The mixture was stirred for 15 to 20 minutes to fully remove the unreacted metal salt and leave more micropores and mesopores for the subsequent adsorption of trace metal salt solvents. After washing, the product was dried at 70 to 80°C for 5 to 6 hours. After the drying was completed and the temperature was lowered, the product was taken out and ground to obtain ZIF-8 powder. The powder was bottled and placed in a vacuum drying oven for later use.

3. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 2, characterized in that: In step (1), the concentration of 2-methylimidazole is 0.03-0.045 g / mL; the concentration of zinc nitrate hexahydrate is 0.03-0.045 g / mL.

4. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 2 or 3, characterized in that: In step (2), Zn in the precursor solution 2+ The concentration is 0.4~0.8mol / L.

5. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 1 or 2, characterized in that: In step 3, 100 μL of the pre-anchored salt solution of M1 and M2 was adsorbed on every 100 mg of ZIF-8 powder.

6. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 1 or 2, characterized in that: The vacuum drying described in step 3 is vacuum drying at a temperature of 30 to 35° C. for 0.5 to 1 h.

7. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 1 or 2, characterized in that: The protective atmosphere described in step 4 is nitrogen, argon, or a hydrogen-argon mixed gas with a hydrogen volume content of 5% to 10%.

8. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 1 or 2, characterized in that: The amount of protective gas introduced in step 4 is 20-30 ml / min.

9. The method for directional construction of non-precious metal catalysts with high proportion of alloyed diatomic pairs according to claim 1 or 2, characterized in that: The temperature rise in step 4 is 10-30℃min -1 The heating rate is carried out.

Citation Information

Patent Citations

  • Bimetal oxygen reduction catalyst and preparation method thereof

    CN118016917A

  • High-dispersion co-based bimetallic catalyst based on zifs, and preparation method therefor

    WO2022188368A1